Pore pressure inhibits clustering of induced earthquakes in Western Canada - Li, Bing Q. (Proceedings of the National Academy of Sciences - PNAS, 2025)
Induced earthquakes are manifestations of highly heterogeneous distributions of effective stress changes imparted by anthropogenic activities such as hydraulic fracturing and wastewater injection. It is critical to disentangle the mechanisms behind these earthquakes to better assess seismic risk. Here, a clustering methodology is applied to a catalog of 21,536 induced earthquakes detected during a 36-d hydraulic stimulation program in Western Canada. The results reveal that clustered events nucleate at short recurrence times generally less than 6 min. Notably, the clustered events are not characterized by short interevent distances as seen in regional-scale studies. Numerical modeling reveals that earthquakes cluster preferentially in regions of significantly lower pore pressure change ( Δ P ). Furthermore, clustered earthquakes exhibit significantly more chain-like topologies with decreasing Δ P , in agreement with laboratory studies showing that fault materials transition to rate-strengthening behavior with increasing Δ P . Proxy estimates for pore pressure change suggest these observations are consistent across Western Canada, and highlight the potential for significant temporal segmentation of induced earthquake processes.